2020
DOI: 10.3390/md18080394
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Bioactivities of Quadrangularisosides A, A1, B, B1, B2, C, C1, D, D1–D4, and E from the Sea Cucumber Colochirus quadrangularis: The First Discovery of the Glycosides, Sulfated by C-4 of the Terminal 3-O-Methylglucose Residue. Synergetic Effect on Colony Formation of Tumor HT-29 Cells of these Glycosides with Radioactive Irradiation

Abstract: Thirteen new mono-, di-, and trisulfated triterpene glycosides, quadrangularisosides A–D4 (1−13) have been isolated from the sea cucumber Colochirus quadrangularis, which was collected in Vietnamese waters. The structures of these glycosides were established by 2D NMR spectroscopy and HR-ESI (High Resolution Electrospray Ionization) mass spectrometry. The novel carbohydrate moieties of quadrangularisosides D–D4 (8−12), belonging to the group D, and quadrangularisoside E (13) contain three sulfate groups, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
(196 reference statements)
1
13
0
Order By: Relevance
“…Analyzing the majority of tested compounds, it has been revealed that the membranes of erythrocytes are more sensitive to the glycoside membranolytic action than the other tested cells such as mouse spleen lymphocytes, ascites of mouse Ehrlich carcinoma, and neuroblastoma Neuro 2a or normal epithelial JB-6 cells. This regularity was observed in the glycosides of the Actinocucumis typica [23], Colochirus robustus [24], Massinium magnum [25,26], Eupentacta fraudatrix [27][28][29], Psolus fabricii [30,31], and Colochirus quadrangularis [32] sea cucumbers. One of the explanations for this phenomenon may be the enrichment of red blood cell membranes with cholesterol [10].…”
Section: Structure-activity Relationships (Sar) Observed In the Glycosides From Sea Cucumbersmentioning
confidence: 74%
See 3 more Smart Citations
“…Analyzing the majority of tested compounds, it has been revealed that the membranes of erythrocytes are more sensitive to the glycoside membranolytic action than the other tested cells such as mouse spleen lymphocytes, ascites of mouse Ehrlich carcinoma, and neuroblastoma Neuro 2a or normal epithelial JB-6 cells. This regularity was observed in the glycosides of the Actinocucumis typica [23], Colochirus robustus [24], Massinium magnum [25,26], Eupentacta fraudatrix [27][28][29], Psolus fabricii [30,31], and Colochirus quadrangularis [32] sea cucumbers. One of the explanations for this phenomenon may be the enrichment of red blood cell membranes with cholesterol [10].…”
Section: Structure-activity Relationships (Sar) Observed In the Glycosides From Sea Cucumbersmentioning
confidence: 74%
“…It became obvious that glycosides cytotoxic activity depends structures, but also on the type of processed cells differing by compo peculiarities of their membranes [1]. Analyzing the majority of tested been revealed that the membranes of erythrocytes are more sensit membranolytic action than the other tested cells such as mouse spleen of mouse Ehrlich carcinoma, and neuroblastoma Neuro 2a or normal This regularity was observed in the glycosides of the Actinocucumis t robustus [24], Massinium magnum [25,26], Eupentacta fraudatrix [27][28][29], and Colochirus quadrangularis [32] sea cucumbers. One of the ex phenomenon may be the enrichment of red blood cell membranes with…”
Section: Structure-activity Relationships (Sar) Observed In the Glycosides Fromentioning
confidence: 92%
See 2 more Smart Citations
“…Quadrangularisosides A 1 , C, C 1 , and E possessed strong inhibitory activity on colony formation in HT-29 cells. Due to the synergic effects of these glycosides (0.02 µM) and radioactive irradiation (1 Gy), a decreasing number of colonies was detected [18]. The second article concerns the isolation and structural elucidation of six new monosulfated triterpene tetra-, penta-and hexa-osides, namely, kurilosides A 1 , A 2 , C 1 , D, E, and F, as well as the known earlier kuriloside A, with unusual non-holostane aglycones without lactone, from the sea cucumber Thyonidium (= Duasmodactyla) kurilensis (Levin) (Cucumariidae, Dendrochirotida), collected in the Sea of Okhotsk near Onekotan Island from a depth of 100 m. Structures of the glycosides were elucidated by 2D NMR spectroscopy and HR-ESI mass spectrometry.…”
mentioning
confidence: 99%